The ANALISIS MANAJEMEN PEMBIAYAAN DI MTS YPKM AL-HIDAYAH: ANALISIS MANAJEMEN PEMBIAYAAN DI MTS YPKM AL-HIDAYAH - Rohaeni, Imas; Suryadi; Fitroh Hayati (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
This study analyzes financial management at MTs YPKM Al-Hidayah, a private Islamic school in Bandung Regency, focusing on the implementation of electronic-based financial management systems (eRKAM) and the effectiveness of School Operational Assistance (BOS) fund utilization. Using a descriptive qualitative method, this research collected data through participatory observation, in-depth interviews, and documentation study. The results show that the school has high dependency on BOS funds as the main funding source, with total receipts of IDR 224,640,000 in 2024. eRKAM implementation has improved efficiency and transparency in financial management, despite facing challenges in system adaptation. Budget allocation prioritizes learning development, educational assessment, and infrastructure. Financial supervision is implemented through structured monitoring mechanisms and periodic audits. The main constraints lie in limited funding sources and operational needs complexity. Development strategies focus on funding source diversification and financial management competency improvement. This research contributes to the development of effective and sustainable madrasah financial management models.